LINGUPOETICS OF FIGURAL THEONIMS (Bulletin of Innovative Research, 2026)
The article discusses the expression of the concept of the Creator through metaphorical transfer based on the beauties of the mythological characters Hur and Pari, the role of figurative-metaphorical transfer and artistic-aesthetic thinking in expressing the theonymic meaning.